Kedudukan Kepala Desa Dalam Tindak Pidana Korupsi Menurut Undang-Undang Nomor 31 Tahun 1999 Jo Undang-Undang Nomor 20 Tahun 2001 Tentang Pemberantasan Tindak Pindana Korupsi - Syahban; Hotma P. Sibuea; Ika Dewi Sartika Saimima (Jurnal Hukum Sasana, 2021)
The position of the Village Head as a legal subject in law number 31 of 199 in conjunction with law number 20 of 2001 regarding corruption is not found. In this law, the legal subjects regulated in Article 1 include corporations, state administrators, civil servants and individuals. The legal vacuum in the criminal act of corruption is certainly a problem, if the village head collides with Articles 5, 11, 12 and 12 B. The problem in this research is about; Village heads have legal status as civil servants or state administrators. The ideal legal status of the Village Head in the context of the corruption law? The purpose of this study was to investigate whether the village head could be categorized as a civil servant or state administrator as referred to in law number 31 of 1999 jo law number 20 of 2001 concerning the eradication of corruption. Second, to find out the ideal legal status of the village head in law number 31 of 1999 in conjunction with law number 20 of 2001 concerning the eradication of corruption. The research method used in this research is the normative juridical research method. This study shows the following results. First, the position of the Village Head cannot be categorized as having the legal status of a Civil Servant or State Administrator as referred to in law number 31 of 1999 in conjunction with law number 20 of 2001 concerning the eradication of criminal acts of corruption. Second, the ideal legal status of the village head in relation to law number 31 of 1999 in conjunction with law number 20 of 2001 concerning the eradication of corruption is as state administrator. Suggestions that can be conveyed are as follows. First, law number 31 of 1999 in conjunction with law number 20 of 2001 concerning the eradication of corruption does not explain the legal position of the village head, whether as a civil servant or state administrator. So, to reinforce the legal position of the village head, revisions or changes need to be made. Second, in the revision or amendment of law number 31 of 1999 in conjunction with law number 20 of 2001 concerning the eradication of corruption, it is necessary to add or insert one paragraph regulating the legal status of the village head, namely as state administrator.